Educational technologies in times of social isolation: a research with teachers (Research, Society and Development, 2020)
Educational technologies do not present themselves as unprecedented in this second decade of the century, however, the use of it may be unprecedented for many teachers in 2020 due to the presence of the world pandemic, known as COVID-19. The need for social isolation forced even many education professionals to adapt to the use of technological tools in the teaching-learning process. The objective of the research is to analyze the methodological process used by a group of teachers from the IFSC-Araranguá in time of COVID-19, proposing to identify the best teaching tools. The theoretical basis addresses teaching methods with a focus on technological use, as well as the profile of the teacher and student in this process. The methodology used is qualitative research and the results obtained address teachers' perceptions in relation to the methods used in education in times of pandemic, teaching-student relationship in relation to online education methods and expectations of the future of education. It is concluded that the answers obtained lead to the strengthening of the already disseminated idea that it will not return to what was called "normal", but rather if it is building together a "new normal", also in the educational area.